Novel nucleoside analogues targeting HCV replication through an NS5A‐dependent inhibition mechanism. (24th March 2017) - Lougiakis, Nikolaos; Frakolaki, Efseveia; Karmou, Panagiota; Pouli, Nicole; Marakos, Panagiotis; Madan, Vanesa; Bartenschlager, Ralf; Vassilaki, Niki
Abstract : A series of new tricyclic nucleosides were synthesized and evaluated as hepatitis C virus (HCV) replication inhibitors. Initial screening in a HCV replicon system, derived from a genotype 1b isolate, identified 9‐benzylamino‐3‐(β‐D‐ribofuranosyl)‐3 H ‐imidazo[4′, 5′:5, 6]pyrido[2, 3‐ b ]pyrazine (15d ) as the most potent analogue. Comparative assessment of15d activity against HCV full‐length viruses or subgenomic replicons derived from genotypes 1 to 4 revealed a specificity of the compound for genotypes 1 and 3. Surprisingly, resistance mutations selected against15d were mapped to domains II and III of the non‐structural protein 5A (NS5A), but not to the RNA‐dependent RNA polymerase residing in NS5B. These results argue that compound15d might represent a lead for the development of a novel class of NS5A inhibitors. Abstract : A number of new tricyclic nucleosides were synthesized and their inhibitory potential against HCV was evaluated. The benzylamino derivative15d reduced HCV replication and possessed selectivity index 4.97 in 1b genotype. Resistance mutation studies were performed, suggesting that this compound could possess a NS5A‐dependent mechanism of action, which is unexpected for nucleoside derivatives.